Teacher leadership in Lithuania : are teachers prepared to cooperate? - Brandisauskiene, Agne (Array, 2019)
Over the past 25 years, Lithuania has established a system of education based on humanistic and democratic relationships. In this system, teacher leadership is highly important, as it serves as the basis for school community “reculturisation” and improvement. The aim of the current article is to overview the situation of teacher leadership in Lithuania, emphasising the aspect of teacher cooperation. The three characteristics of Lithuanian teacher leadership that we present demonstrate that teacher cooperation remains a challenge in the country. Teachers are reluctant to discuss and render improvement proposals, and lack experience of teamwork. Nevertheless, it is to be expected that the ongoing project “Time for Leaders,” will produce the necessary cultural change required to create a learning network of teachers and establish genuine, open and professional dialogue.